Studi Pengaruh Kualitas Jalur Pedestrian terhadap Tingkat Sense of Place Sebuah Kasus di Pusat Kota Banda Aceh - Martin Martin; Elysa Wulandari; Muliadi Muliadi (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
Banda Aceh as the capital city of Aceh province has been the capital since the royal era and continues to grow, especially kawasan simpang lima which is strategic because it connect 5 primary roads in Banda Aceh city, one of them is st. Teuku Panglima Polem, it is a primary road that connected to some multi-culture village as a commercial area and chinatown. Teuku Panglima Polem road should be grow with a variety of cultures that seen in the city elements. However, based on observation, the feel of cultural diversity as a sense of place of Teuku Panglima Polem street’s pedestrian ways is less pronounced. This study aims to identify the level of sense of place, to test and analyze the influence of pedestrian ways towards sense of place, and to give solution on problem of sense of place. This study is a causal associative study with quantitative method. The data collection methods are distribution of questionnaries, observation, unstructured interview, and literature studies. The sampling method is non-probability sampling using purposive sampling technique. Data analysis technique are using statistics descriptive analysis and multiple linear regression analysis. The result of this study is the level of sense of place on st. Teuku Panglima Polem is “belonging to a place”, the pedestrian ways has a significant positive influence towards the sense of place, and the visualization of design recommendation.